Keterlibatan Mahasiswa dalam KKN Berbasis Masjid dan Dampaknya terhadap Pengembangan Sosial Ekonomi di Masyarakat Lokal Dusun 1 Desa Bukit Peninjauan II - Dari, Tri Wulan; Romadina, Sinta; Agustifani, Anita; Ilahi, Indra Dewa Sahda; Putri, Adella Septika; Zadia, Halimatu; Jerlyanto, Jerlyanto; Hardiansyah, Renaldi; Eriz, Gressia Julia; Agustina, Fania; Nurhidayat, Nurhidayat (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This article aims to assist the local community in advancing the economy through training and development. The improvement of welfare and prosperity of a country’s society is closely related to the level of economic development that is undertaken. This activity implements the Digital Marketing method, which is marketing through social media. Digital Marketing is one of the most influential marketing methods.The results and discussion refer to the implementation methods of the activities that have been designed, namely: the publication of MSMEs in Bukit Peninjauan II Village, Dusun I, and the grand seminar of KKN in Bukit Peninjauan II Village, Dusun I. Based on the results of the activities carried out by KKN students in Bukit Peninjauan II Village, Dusun I, it can be concluded that the outreach seminar provides additional insights and new knowledge for the community, especially for community leaders who have interests.